Pengaruh Dewan Komisaris dan Profitabilitas terhadap Kinerja Keuangan pada Perusahaan Sektor Industri di BEI Periode 2021-2024 - Nidia Anggreni Das; Siska Yulia Defitri; Hidayanti Fitra; Chintya Maharani; Natasya Natasya; Marisa Penriani; Tevi Putri (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of board size and profitability on the financial performance of industrial companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. Board size is measured by the number of board members, while profitability is proxied by Return on Assets (ROA). Financial performance is assessed using Return on Equity (ROE), a common metric for evaluating the effectiveness of a company’s operations. The study population includes all industrial companies listed on the IDX during the specified period. The sampling technique employed is purposive sampling, which selects a representative sample based on specific criteria relevant to the study. Data for the analysis were sourced from the annual financial reports published by the companies. Panel data regression analysis was used for data analysis, supported by statistical software, to explore the relationship between the independent variables (board size and profitability) and the dependent variable (financial performance). The study finds that board size and profitability are crucial factors that can influence the financial performance of industrial companies. Larger boards may contribute to better decision-making and governance, while higher profitability can indicate efficient use of resources and positively affect financial outcomes. The results of this study are expected to provide empirical evidence on the role of corporate governance, particularly regarding board size and profitability, in shaping the financial performance of industrial companies in Indonesia. By understanding these relationships, the study aims to contribute to the broader discussion on improving corporate governance and financial performance in emerging markets.